2007
DOI: 10.2478/v10019-007-0031-8
|View full text |Cite
|
Sign up to set email alerts
|

In vivo dosimetry with diodes in rectal cancer patients

Abstract: regarding actual treatment delivery. It is understandably considered an indispensable quality assurance procedure and a safety measure in the treatment process. 1-3 This paper describes the calibration of dosimetric diodes and presents the results of in vivo dosimetry in 209 rectal cancer patients. 4 Materials and methods Calibration Two dosimetric diodes EDP-20, manufactured by Scanditronix, were calibrated

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 4 publications
1
0
0
Order By: Relevance
“…The results of this method in the patient study involving 25 cervical cancer patients is comparable with the results obtained with other in-vivo dosimeters. The standard deviation of ±2.9% along with mean dose reported by Mortan JP et al [14] using MOSFET for pelvis patients, SD of ±1.4% reported by Andrej Strojnik [15] using diodes and SD of ±2.6% by Alessandro M.Costa using TLD [16] are comparable with the SD values obtained in this study. Gandhi MA et al [17] using diodes in rectal cancer have shown that 86.493% of measurements are within ±3%, are comparable with our results of 83.2% for individual measurements and 92% for the average dose for 5 fractions.…”
Section: Resultssupporting
confidence: 90%
“…The results of this method in the patient study involving 25 cervical cancer patients is comparable with the results obtained with other in-vivo dosimeters. The standard deviation of ±2.9% along with mean dose reported by Mortan JP et al [14] using MOSFET for pelvis patients, SD of ±1.4% reported by Andrej Strojnik [15] using diodes and SD of ±2.6% by Alessandro M.Costa using TLD [16] are comparable with the SD values obtained in this study. Gandhi MA et al [17] using diodes in rectal cancer have shown that 86.493% of measurements are within ±3%, are comparable with our results of 83.2% for individual measurements and 92% for the average dose for 5 fractions.…”
Section: Resultssupporting
confidence: 90%